A Bibliometric Analysis of Sustainable Supply Chain Finance Research - Loso Judijanto (Westscience Press, 2026)
This study presents a bibliometric analysis of sustainable supply chain finance (SSCF) research to map its intellectual structure, evolution, and emerging trends. By examining a dataset sourced from Scopus and Web of Science, the study employs VOSviewer to visualize keyword co-occurrence, author collaborations, and thematic developments within SSCF literature. The results reveal a significant shift towards integrating financial mechanisms with sustainability goals, with a growing focus on